Analisis Kelayakan Usaha Menggunakan Diskonto dan Tanpa Diskonto UMKM ‘’HS Styrofoam’’ (Studi Kasus di Desa Pekalongan, Kecamatan Pekalongan, Lampung Timur, Lampung) - Hafitsah, Nazila; Fadhilah, Indah; Sovia, Sabrina Tiara; Ramadhani, Novia Nazila; Shihab, Nazwa; Dian Fajarini (Goodwood Publishing, 2025)
This study aims to analyze the business feasibility of the Kedai Sera This study aims to assess the business feasibility of HS Styrofoam in Lampung Timur using discounted and non-discounted financial analysis methods. The business supplies styrofoam decorations to meet increasing demand for creative and cost-efficient event decor. The study uses secondary data from projected financial reports (2021–2024). Results indicate that the business is financially feasible. The Net Present Value (NPV) is positive at Rp36,999,066, the Internal Rate of Return (IRR) is 29.14%, and the payback period is only 1.53 years. Other indicators also exceed standard thresholds for efficiency and profitability. Therefore, HS Styrofoam is an efficient and profitable business with fast capital recovery and strong potential for development.